DYE-COUPLING IN THE ROOT EPIDERMIS OF ARABIDOPSIS IS PROGRESSIVELY REDUCED DURING DEVELOPMENT - Duckett, C; Oparka, K; Prior, D; Dolan, L; Roberts, K (1994)
Epidermal cells of the Arabidopsis thaliana root are derived from a ring of 16 or so initials (stem cells) that are located just below the quiescent centre of four central cells. Derivatives of these initials divide transversely in the meristematic region of the root to produce files of cells that subsequently elongate and differentiate. There are two kinds of cell file in the epidermis, hair cells and non-hair cells, that are organised in an ordered pattern and become distinguishable within a few divisions of the initials. It is likely that local intercellular communication plays an important role in the early establishment of this pattern, enabling cells to register their position and fate. We have therefore examined the extent to which cells in the root apex are symplastically coupled through plasmodesmata. Using a variety of dye loading methods we show that the undifferentiated cells are dye-coupled i.e. cells in the meristem and the elongation zone are symplastically connected, but that cells gradually become symplastically isolated as the cells differentiate. By the time that visible hair outgrowth is observed the cells of the epidermis are symplastically isolated. This resembles the pattern of gap-junction connectivity observed in many animal systems where cells are coupled at the stage that cell patterns become established, but become progressively more isolated as they differentiate.